ENGLISH INFLECTIONAL ERRORS MADE BY INDONESIAN DEAF PEOPLE IN COMPOSITION - Suwandi Suwandi; Deliana Deliana; Desri Maria Sumbayak (Jurnal Bahastra, 2017)
This research entitled ‘English Inflectional Errors Made by Indonesian Deaf People in Composition’ was conducted with the aims to describe what types of English inflectional errors are found in Indonesian deaf people in writing composition, identify what sources of the errors are found in the use of English inflection, and to find out the percentages. The Indonesian deaf people were from Indonesian deaf community groups on Facebook, WhatsApp, and Instagram. This research used a descriptive qualitative approach by applying English inflection theory by Andrew Carstairs-McCarthy. The data collection techniques were conducted by using online English writing test and documentation. The documents used to support this study were in the form of downloaded word files that showed the Indonesian deaf people’s online test responses. The results showed that there are 179 errors in total in Indonesian people’s writings. The error found most is in Third Person Singular Present Inflection with 51 errors (28.5%) and the least is in Present Participle Inflection with 16 errors (9%), and the rest are 18 errors (10%) in Preterite Inflection, 19 errors (10.6%) in Comparative Inflection, 22 errors (12.3%) in Superlative Inflection, 27 errors (15.1%) in Past Participle Inflection, and 26 errors (14.5%) in Plural Inflection. The source of error found most is Intralingual Error with 156 errors (87.15%) (False Concept Hypothesized with 6 errors (3.3%), Incomplete Application of Rules with 8 errors (4.5%), Overgeneralization with 23 errors (12.85%), and Ignorance of Rules Restriction with 119 errors (66.5%)) and Interlingual Error with 23 errors (12.85%). Ignorance of Rule Restriction is a source of error found most and False Concept Hypothesized is found least among the Interlingual errors and all the sources of errors.Keywords: Deaf People, Error Analysis, English Inflection